Benchmark tests on high strength steel frames. (1st May 2022) - Yun, Xiang; Zhu, Yufei; Wang, Zhongxing; Gardner, Leroy
Highlights: Eight large-scale frames made of S690 welded I-sections were tested. Digital Image Correlation was employed to obtain detailed information. Out-of-plane displacement was restrained by using a bespoke lateral bracing system. Test setup, instrumentation, loading procedures and observations were fully described. The potential for plastic design of HSS structures were highlighted. Abstract: Physical experiments are widely used in structural engineering for the validation of finite element models and the establishment and assessment of design provisions. However, while there exists an abundance of member-level test data, there is a clear need for further benchmark frame-level test data, particularly given the growing trend for advanced system-level simulation and design. Towards meeting this need, and exploiting state-of-the-art measurement techniques, tests on eight high strength steel frames are presented herein. The tested frames were fixed-base, single storey, unbraced in-plane and made up of welded S690 steel I-section members. Two section sizes, of different local slenderness, were employed to assess the influence of local buckling on cross-section strength and the potential for plastic redistribution of forces within the frames. All the frames were laterally restrained out-of-plane using a bespoke lateral bracing system, but free to deform in-plane. The frames were subjected to different combinations of horizontal and vertical loading, in order for beam, sway and combined mode mechanisms to form. Extensive use was made of digital image correlation in order to obtain detailed information on the deformation of the frames and their components. The test setup, instrumentation, loading procedures and frame structural response, including load-deformation characteristics, failure modes and connection rotational stiffnesses are fully reported. The experimental data indicated that, despite the lower ductility and strain hardening of HSS relative to normal strength steel (NSS), HSS frames with stocky cross-sections have the ability to form plastic hinges with sufficient rotation capacity to achieve a considerable amount of inelastic moment redistribution; the potential for extending plastic design to HSS structures has therefore been demonstrated. The test results also provide a firm basis for the validation of advanced numerical models and system-level design approaches.